Sinergi Bimbingan Teknis Pembuatan Media Pembelajaran untuk Guru PAUD: Upaya Peningkatan Kualitas Pembelajaran - Muhammad Yusri Bachtiar; Islami, Andi Nur Maharani; Muhammad Akil Musi; Rika Kurnia; Makkasau, Andi (Tasnim Journal for Community Service, 2025)
This community service activity aimed to enhance the competence, understanding, and creativity of PAUD (Early Childhood Education) teachers in designing and developing learning media using simple, low-cost, and environmentally friendly materials. The training was held at TK Annisa, Pattallassang District, Gowa Regency, and involved four teachers from two local PAUD institutions along with students from the Early Childhood Education Department of Universitas Negeri Makassar. This program was conducted as part of the course output for the subject “Media Pembelajaran AUD” and implemented through three main stages: preparation, delivery of conceptual material and hands-on practice, and evaluation using structured questionnaires. The development of learning media was based on thematic learning concepts aligned with the national curriculum for early childhood education. Participants were guided to utilize recycled and reusable materials such as used cardboard, plastic bottle caps, fabric remnants, and other household waste. The findings revealed that the teachers experienced a significant increase in their knowledge and skills, as well as their ability to apply creative ideas into meaningful learning tools. Furthermore, the collaborative process between lecturers, students, and teachers encouraged reflective practice and sustainable innovation. Overall, the program ran effectively and achieved its objectives in supporting professional development for PAUD educators.